Variable plumage coloration of breeding Barbary Falcons Falco (peregrinus) pelegrinoides in the Canary Islands: do other Peregrine Falcon subspecies also occur in the archipelago? - Rodríguez, Beneharo; Siverio, Felipe; Siverio, Manuel; Rodríguez, Airam (Witherby & Co, 2011)
The taxonomic status of the Barbary Falcon has been controversial for many years, it being variously considered a subspecies of Peregrine Falcon (Falco peregrinus pelegrinoides) or treated as a full species (F. pelegrinoides). Although morphological and molecular studies are still scarce, they suggest that subspecific status is more appropriate. Other subspecies of Peregrine, such as F. p. brookei, exhibit some plumage characteristics similar to Barbary Falcon. We quantitatively describe coloration patterns of Barbary Falcons breeding in the Canary Islands, based on photographs of wild birds, injured or dead individuals brought to rehabilitation centres, and specimens deposited in museum collections. We tested sexual differences, and compared Canaries falcons with a sample of specimens labelled as F. p. brookei. Males of both taxa are usually paler and possess less barred underparts than females. The majority (>60%) of birds in the Canaries have a Barbary Falcon-like appearance, but there is much overlap with F. p. brookei. This variation in coloration could be natural or relate to escaped falconry birds, meaning that molecular studies are needed to clarify the identity of wild falcons on the Canary Islands. Peer reviewed